2019
DOI: 10.1186/s12891-019-2655-4
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal trunk muscle weakness and its association with chronic low back pain and risk of falling in older women

Abstract: Background Previous studies have indicated that trunk muscle strength decreases with chronic low back pain, and is associated with poor balance, poor functional performance, and falls in older adults. Strengthening exercises for chronic low back pain are considered the most effective intervention to improve functional outcomes. We developed an innovative exercise device for abdominal trunk muscles that also measures muscle strength. The correlation between muscle weakness, as measured by our devic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 30 publications
(31 reference statements)
0
46
0
5
Order By: Relevance
“…Second, we expected that the adoption of ASMI but not trunk muscle mass in AWGS 2019 sarcopenia criteria 4 is responsible for the ambiguous correlation between LBP and sarcopenia in community‐dwelling older adults. Trunk muscle weakness is predominantly associated with the development of LBP, 5,8,10 although ASM is positively associated with trunk muscle mass. In a cross‐sectional analysis from a prospective cohort study of Japanese local residents, Tanishima et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, we expected that the adoption of ASMI but not trunk muscle mass in AWGS 2019 sarcopenia criteria 4 is responsible for the ambiguous correlation between LBP and sarcopenia in community‐dwelling older adults. Trunk muscle weakness is predominantly associated with the development of LBP, 5,8,10 although ASM is positively associated with trunk muscle mass. In a cross‐sectional analysis from a prospective cohort study of Japanese local residents, Tanishima et al .…”
Section: Discussionmentioning
confidence: 99%
“…reported that muscle atrophy might lead to chronic LBP at multiple levels of the lumbar spine 9 . Several studies have indicated that atrophy of the back muscles is a significant factor that causes LBP 5,8,10 . Recent reports suggest that there is a relationship between sarcopenia, frailty and a specific orthopedic disease that causes LBP 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…proprioceptive losses, weakening of lower-extremity sensory feedback, and trunk muscle weakness and atrophy [26,28,29,32] . Thus, when aging is combined with LBP, impaired motor performance and balance dysfunction worsen.…”
Section: Discussionmentioning
confidence: 99%
“…Following the title andabstract screening, 35 fulltext articles were retrieved. The full-text review was completed to determine nal inclusion; 17 articles (13 case-control studies [20][21][22][23][24][25][26][27][28][29][30][31][32] , four RCTs [33][34][35][36] ) met the inclusion criteria. Only the 13 case-control studies were included in the meta-analysis.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation